PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Suardika, I Ketut; Heni, Heni; Anse, La (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
The purpose this research to improve the learning outcomes of class VB students of SD Negeri 51 Kendari through the application of the Project Based Learning (PjBL) model on the theme of events in life. Research procedures, using steps: (a) planning, (b) implementation of action, (c) observation and evaluation, (d) reflection. Types of data are qualitative and quantitative data. Qualitative data were obtained through observation sheets while qualitative data were obtained through learning outcomes tests. The results showed that students who achieved learning completeness in the first cycle were 18 people with a percentage of 64.2% while the number of students who did not complete was 10 people with a percentage of 35.7%. The average student learning outcomes in cycle I was 71 while in cycle II student learning outcomes increased, consisting of 24 students who got a complete score with a percentage of completeness of 85.7%, while the number of students who did not complete was 4 people with a percentage of 14.2%. The average value of student learning outcomes in cycle II is 77